THE QUANTITY AND QUALITY OF INTERCEPTION IN EUCALYPTUS (EUCALYPTUS UROPHYLLA), MAHONI (SWIETENIA MACROPHYLLA) AND TREMBESI (SAMANEA SAMAN) - Fikri Fadhilah, Muhamad
Increasing the number of population in urban areas will cause more and more use of natural resources. This condition can lead the increasing use of land resources in urban areas in the form of Green Open Space which is converted into built land. This results cause the increase of surface runoff, so that the risk of catastrophic flooding will increase. For this reason, the existence of urban vegetation cover in the form of green space is considered important as protection from floods and erosion. In addition, it is also known that rainwater that has been intercepted by vegetation cover is able to enrich the organic elements carried by rainwater. The purpose of this research is to study the characteristics of trees in intercepting rain and their effects on the quality of rainwater. There are 3 types of trees to be tested, namely Eucalyptus urophylla, Swietenia macrophylla and Samanea saman. The type of data that are going to be collected are tree dimensions, rainfall interception, and water quality. Interception measurement is done by counting the number of throughfall and stemflow for one month. While the measurements of interception water quality are measured only once in the laboratory. These water quality measurements include EC, hardness, elemental contents of Ca, Mg, Na and K, and pH concentration. The results showed that based on the total canopy area, eucalyptus had an interception value of 30.06% followed by rain tree and mahogany respectively 27.67% and 18%. Whereas based on the ability of interception wide unit (m2) the eucalyptus has the highest interception base ability of 10,046x10?6 mm /m2, while the species with the lowest interception base ability are rain tree which is 3,241x10?6 mm / m2. In the measurement of Throughfall, the type of mahogany is the tree that has the largest throughfall with 81.79% and the lowest is the eucalyptus with 69.8%. Then the eucalyptus shows the highest percentage of stemflow with a value of 0.131% and rain tree is the one with the lowest stem flow with only 0.037%. The results of the study show that the relationship between the value of interception, throughfall and stemflow with rainfall in general can be said to be real and positively correlated. Where the higher the rainfall, causes the higher of the value of interception, throughfall and stemflow. The results of the measurement of water quality shown if the value of EC on rainwater interception results generally decreased from the rainfall water, except in the mahogany trees. Same condition are also happen in the level of hardness water. In the measurement of pH, water from interception in all three tree species decreased compared to direct rainfall water. In addition, for the elemental content of Ca, Mg, K and Na in rainwater the interception of the three tree species generally increased compared to control rainfall. The highest addition of chemical elements (Ca, Mg, K and Na) occurs in the mahogany’s throughfall.